RANCANG BANGUN SISTEM INFORMASI RESERVASI HOTEL GRAND VIEW KOTA JAYAPURA - Daniel Bienfield Manahan Siahaan; Emy Lenora Tatuhey (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
The hotel industry is increasingly required to provide fast, accurate, and efficient services. Hotel Grand View Jayapura still uses a manual reservation system that causes service delays, risks of recording errors, and limited access for customers. This study aims to design and build a web-based hotel reservation information system to improve service quality and operational efficiency. The development method used is the Waterfall method, which consists of the stages of needs analysis, design, implementation, and testing. The system was developed using the PHP, HTML, CSS programming language and tested using the blackbox method to ensure its functionality runs according to needs. The test results show that the system can manage customer data, rooms, reservations, and payments in an integrated and valid manner. With this system, the reservation process becomes faster and more transparent, and can reach more customers online. This system is expected to support digital transformation at Hotel Grand View Jayapura.